1989
DOI: 10.1007/bf01536055
|View full text |Cite
|
Sign up to set email alerts
|

Impaired oxygenation of gastric mucosa in portal hypertension

Abstract: Increased susceptibility to mucosal damage is a prominent feature of portal hypertensive gastropathy. Since the portal hypertensive gastric mucosa has extensive microvascular changes, we postulated that the increased sensitivity to mucosal damage could have an ischemic basis. We measured distribution of gastric serosal and mucosal oxygenation in a group of portal hypertensive and sham-operated rats, and then studied the effects of intragastric aspirin. In the basal state, gastric mucosa of portal hypertensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
43
0
3

Year Published

1992
1992
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(48 citation statements)
references
References 11 publications
2
43
0
3
Order By: Relevance
“…In portal hypertension, there is splanchnic vasodilatation and arteriovenous shunts development in the submucosa which leads to increased blood flow in this area. This increases the risk of bleeding and at the same time decreases oxygenation of the mucosa with consequent risk of damage 15,16 . The related thrombocytopenia and coagulopathy may also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…In portal hypertension, there is splanchnic vasodilatation and arteriovenous shunts development in the submucosa which leads to increased blood flow in this area. This increases the risk of bleeding and at the same time decreases oxygenation of the mucosa with consequent risk of damage 15,16 . The related thrombocytopenia and coagulopathy may also be involved.…”
Section: Discussionmentioning
confidence: 99%
“…1,[3][4][5] The microvascular abnormalities have been implicated in the increased susceptibility of PHT gastric mucosa to damage. [4][5][6][7][8] Excessive production of nitric oxide (NO) by endothelial NO synthase (eNOS) has been suggested as the basis for the systemic hyperdynamic and abnormal circulation of PHT gastric mucosa. [9][10][11][12] Tumor necrosis factor ␣ (TNF-␣) has been shown indirectly to be a major contributor to the hyperdynamic circulation likely through activation of NO synthase.…”
mentioning
confidence: 99%
“…[1][2][3] The PHT gastric mucosa has distinct morphological and functional abnormalities that increase its susceptibility to damage by noxious factors such as alcohol, aspirin, and ischemia/reperfusion. [4][5][6][7][8][9] We have recently showed that nitric oxide synthase isoform 3 (NOS3) messenger RNA (mRNA) and protein are overexpressed in PHT gastric mucosa of rats, and this overexpression may be, at least in part, responsible for the increased susceptibility of PHT gastric mucosa to damage. 10 However, the mechanisms that activate NOS3 in PHT gastric mucosa are unknown.…”
mentioning
confidence: 99%